Bringing a Horse to Water: The Shaping of a Child Successor in Family Business Succession - Wasim, Jahangir; Almeida, Fernando (European Journal of Family Business, 2022)
This study critically investigates and evaluates the childhood and adolescent year strategies, and efforts that parent-owners of family businesses incorporate to encourage and prepare children for a successful future succession. The sample consisted of six family businesses in the North East of Scotland: two successfully introduced a second-generation, two a third generation and one a fourth generation, with one still in the founder stage. The findings reveal that the succession planning process was an instantaneous event into generational bridging, where no formal planning process was commenced. Parent-owners influenced and facilitated knowledge transfer and education, leaving control to the child successors with career options. The research has also shown the difficulties in how the child successors of the future may find succession challenging and demanding with contextually complex issues.